Testing an Optimal Matching Hypothesis of Stress, Coping and Health: Leisure and General Coping - Iwasaki, Yoshi (Loisir et Société / Society and Leisure)

(untitled) (Presses de l’Université du Québec, 2001)
AbstractThe present study focused on examining different ways in which various coping strategies helped university students manage different types of stressful events and promote positive coping outcomes (e.g., coping effectiveness, emotions, health, and well-being) in their daily lives. The study adopted and tested an optimal matching model of stress and coping and used a repeated-assessment field approach. According to the participants’ descriptions and appraisals of events, daily hassles were classified into several groups: (a) academic stressors, (b) interpersonal stressors, (c) uncontrollable or less controllable stressful events, (d) controllable stressful events, and (e) stressful events damaging one’s self-esteem.Overall, the findings support the optimal matching model. A match or fit between the demand of a stressor and the function of a coping strategy tended to result in positive outcomes.A wider range of leisure coping strategies provided more positive outcomes for dealing with various types of daily hassles than general coping strategies (not directly associated with leisure) did. Some types of coping strategies (e.g., positive reinterpretation, leisure empowerment, and leisure mood enhancement) had a positive impact on managing all or many of the different types of stressful events experienced.